SOCIO-HYGIENIC FACTORS IN THE DEVELOPMENT OF CHRONIC LIVER DISEASES: A COMPREHENSIVE EPIDEMIOLOGICAL ANALYSIS - Jalolov N. N.; Norqulov S. J. (American Journals Publishing, 2025)
Chronic liver diseases (CLDs) constitute a group of nosological entities that pose a serious threat to public health on a global scale. In recent decades, alongside viral factors, the contribution of socio-hygienic determinants to the etiological structure of these diseases has increased markedly. This article provides a comprehensive epidemiological analysis of the role of socioeconomic status, dietary patterns, lifestyle, psycho-emotional stress, working and living conditions, and access to healthcare services in the development of chronic liver diseases. Based on global statistical data, cohort studies, and meta-analyses, the significant impact of socio-hygienic factors on the onset, progression, and prognosis of liver pathologies is scientifically substantiated.
Keywords: Chronic liver diseases, social determinants, hygienic factors, epidemiological analysis, liver fibrosis, health inequality.